ROS-scavenging materials for skin wound healing: advancements and applications - Dong, Yongkang; Wang, Zheng (Frontiers in Bioengineering and Biotechnology, 2023)
The intricate healing process of skin wounds includes a variety of cellular and molecular events. Wound healing heavily relies on reactive oxygen species (ROS), which are essential for controlling various processes, including inflammation, cell growth, angiogenesis, granulation, and the formation of extracellular matrix. Nevertheless, an overabundance of reactive oxygen species (ROS) caused by extended oxidative pressure may result in the postponement or failure of wound healing. It is crucial to comprehend the function of reactive oxygen species (ROS) and create biomaterials that efficiently eliminate ROS to enhance the healing process of skin wounds. In this study, a thorough examination is presented on the role of reactive oxygen species (ROS) in the process of wound healing, along with an exploration of the existing knowledge regarding biomaterials employed for ROS elimination. In addition, the article covers different techniques and substances used in the management of skin wound. The future prospects and clinical applications of enhanced biomaterials are also emphasized, highlighting the potential of biomaterials that scavenge active oxygen to promote skin repair. This article seeks to enhance the understanding of the complex processes of ROS in the healing of wounds and the application of ROS-scavenging materials. Its objective is to create novel strategies for effective treatment skin wounds.